Phosphocreatine Attenuates Isoproterenol-Induced Cardiac Fibrosis and Cardiomyocyte Apoptosis. (8th January 2019) - Dai, Hui; Chen, Liang; Gao, Dongyue; Fei, Aihua
Abstract : The present study was designed to further explore the role and the underlying molecular mechanism of phosphocreatine (PCr) for cardiac fibrosis in vivo . Isoproterenol (ISO) was used to induce cardiac fibrosis in rats. PCr administration ameliorated fibrosis by reducing collagen accumulation and fibrosis-related signals, including transforming growth factor beta 1 (TGF- β 1), alpha smooth muscle actin ( α -SMA), collagen type I, and collagen type III. Mitogen-activated protein kinases (MAPKs) and nuclear factor kappa B (NF- κ B) signaling pathways, including p38, extracellular signal regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p65, were highly activated by ISO and blocked by PCr. Moreover, PCr decreased ISO-induced matrix metalloproteinase-9 (MMP-9) and increased the tissue inhibitor of metalloproteinase-1 (TIMP-1) expression. Furthermore, PCr suppressed cardiomyocyte apoptosis induced by ISO, as shown by downregulated expression of the proapoptotic caspase-3, Bax, and upregulated expression of the antiapoptotic Bcl-2. Taken together, PCr can be an effective agent for preventing cardiac fibrosis and cardiomyocyte apoptosis.